PENGARUH LAYANAN INFORMASI MENGGUNAKAN MEDIA KOMIK DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS 7 G SMP NEGERI 11 KOTA BENGKULU - Ayu, Putri; Yessy Elita; Arsyadani Mishbahuddin (Consilia : Jurnal Ilmiah Bimbingan dan Konseling, 2023)
This study aims to describe the effect of information services using comic media in increasing the learning motivation of class VII students of SMP Negeri 11 Bengkulu City. The method in this study used an experiment with a one-group pretest-posttest design. The subjects of this study were 30 students from class VII G of SMP Negeri 11 Bengkulu City with an average level of low learning motivation. Sampling using purposive sampling. Data collection techniques in this study used a questionnaire with a Likert scale. Data analysis in this study used a t-test (paired sample t-test). The results obtained in this study indicate an increase in student learning motivation after being given information services using comic media as a treatment. This is indicated by the average score before being given treatment which is 97.5 in the low category and after being given treatment the average score becomes 145 in the high category. The results of the t-test show a value of t = -14.137 and a significant (2-tailed) value of 0.000, which means 0.000 <0.05. Keywords: learning motivation, information services, comic media